2009
DOI: 10.1111/j.1540-6261.2009.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Managerial Incentives and Discretion in Hedge Fund Performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
290
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 511 publications
(326 citation statements)
references
References 90 publications
30
290
2
4
Order By: Relevance
“…As capital has been flowing out in more recent years, there is the beginning of a trend back to quarterly subscriptions and redemptions. Additional reasons for a higher tolerance for lockups and lower liquidity may be found in Agarwal et al (2009) who report that managers who have more discretion as measured by longer lockups and less-frequent redemptions deliver higher returns. The main point is that the increase in the percentages for the longer periods on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As capital has been flowing out in more recent years, there is the beginning of a trend back to quarterly subscriptions and redemptions. Additional reasons for a higher tolerance for lockups and lower liquidity may be found in Agarwal et al (2009) who report that managers who have more discretion as measured by longer lockups and less-frequent redemptions deliver higher returns. The main point is that the increase in the percentages for the longer periods on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the relationship between size and choice of financing source could be endogenous. As the median size of a hedge fund is typically around $25 million (see Agarwal et al 2009), hedge funds may not be able to provide enough capital to large companies, who then have to either issue debt or negotiate a syndicated bank loan. In an attempt to control for this potential endogeneity, we match each case firm with a control firm (bank borrower or a bond issuer) by year, industry at the 2-digit NAICS code level, and size.…”
Section: Distinguishing Characteristics Of Firms Borrowing From Hedgementioning
confidence: 99%
“…We conduct several checks to ensure that the loan initiators in our sample are indeed hedge funds. First, we use the list of hedge funds in the comprehensive database used in Agarwal et al (2009) to match with those found in the news articles from Factiva. Second, we follow Agarwal et al (2010) to also check the websites of the hedge fund companies and their being listed by industry publications such as Hedge Fund Group (HFG), Barron's, Alpha Magazine, and Institutional Investors.…”
Section: Datamentioning
confidence: 99%
“…In practice it has been observed that alpha-opportunities erode with the assets under management (Getmansky, 2012;and Agarwal et al, 2009). Hence, a fund which becomes too big deprives itself of generating a positive alpha.…”
Section: Defining the Alpha As The Return That Agent I Gets In Excessmentioning
confidence: 99%
“…Moreover we can show that alpha-opportunities erode with the assets under management, which is a feature that has been observed for many active portfolio managers, as for example for hedge funds (cf. Getmansky, 2012;and Agarwal, Daniel, & Naik, 2009). In our model this important feature has a very simple explanation.…”
Section: Literature Reviewmentioning
confidence: 99%